Understanding the impact of the Covid-19 pandemic through the lens of innovation. Issue 3 (July 2021) - Gopalakrishnan, Shanthi; Kovoor-Misra, Sarah
In this article, we explore the Covid-19 crisis through the lens of innovation. We focus on the threat and opportunity drivers of innovation, and some of their product/service and process outcomes. We contribute to crisis innovation theory and practice by suggesting that there are two categories of innovation during multi-level crises, such as a pandemic: (1) reactive, threat-driven innovations that are created to contain and respond to organizational problems and disruptions that arise from the crisis; and (2) proactive, opportunity-driven innovations that are created to capitalize on environmental needs and opportunities. We highlight the role of human, physical interdependence in organizations' core technologies that create threats for some organizations and opportunities for others during the pandemic. JEL CLASSIFICATION : O32; O34; H12